The role of vitamin D deficiency and modifiable risk factors in patients with Crohn’s disease - Feng, Xiaoyue; Yin, Qin; Kang, Ying; Jiang, Kang; Xu, Mengqing; Wang, Fangyu (Frontiers in Immunology, 2025)
BackgroundsVitamin D insufficiency is usually seen in Crohn’s disease (CD). Our study aims to determine the risk factors for vitamin D insufficiency in CD patients.MethodsBetween May 2021 and December 2023, we enrolled 102 CD patients and 100 healthy people in our hospital who were eligible for the study. Changes in vitamin D levels were also analyzed. CD patients were divided into active and clinical remission, and further changes in micronutrient and vitamin D levels were analyzed. Lastly, risk factor analysis was conducted using univariate, multivariate, and LASSO regression analysis models.ResultsThe average age of CD patients was 38.91 ± 3.31 years, whereas the average age of the healthy people was 38.64 ± 2.26 years. Vitamin D levels were significantly lower in CD patients than in healthy controls (19.62 ± 2.68 vs. 22.68 ± 4.61), especially for patients with active CD. In 11 patients treated with vedolizumab, compared to the pre-treatment Vedolizumab group, vitamin D levels improved more dramatically post-Vedolizumab therapy. According to univariate analysis, Age (OR: 0.95, 95% CI 0.26-1.33, p=0.01), sex (OR: 0.26, 95% CI 0.25-0.99, p=0.03), recent biologics (OR: 0.54, 95% CI 0.44-1.25, p=0.02), iron (OR: 0.89, 95% CI 0.72-1.62, p=0.02), and total 25-OH vitamin D (OR: 1.25, 95% CI 1.02-1.99, p=0.02) did significantly differ between patients with and without vitamin D deficiency. After controlling for several variables, multivariate analysis revealed that a lower odds ratio was linked to increasing age at diagnosis (OR: 0.12, 95% CI 0.03-0.85, p=0.02), sex (OR: 0.58, 95% CI 0.44-0.95, p=0.01), iron (OR: 0.44, 95% CI 0.11-0.62, p=0.01), and 25-OH vitamin D total (OR: 0.48, 95% CI 0.25-0.95, p=0.03). In addition, Age, time since illness onset, and 25-OH vitamin D were found to be helpful indicators for CD patients using LASSO regression.ConclusionAccording to this study, vitamin D insufficiency was often linked to CD patients with active status and pre-treatment Vedolizumab. Furthermore, Age, time since illness onset, and 25-OH vitamin D were found to be significant risk factors for CD.